Periodic-pulse relativistic magnetron; Technical Physics Letters; Vol. 26, iss. 7 - Butakov L. D.; Vintizenko I. I. Igor Igorevich; Guselnikov V. I.; Dvoretskiǐ M. I.; Isakov P. Ya. Peter Yakovlevich; Kaminsky V. L. Valery Ludvigovich; Mashchenko A. I. Aleksandr Ivanovich; Mityushkina V. Yu. Vera Yurievna; Ryabchikov A. I. Aleksandr Ilyich; Filipenko N. M. Nikolai Maksimovich; Fomenko G. P.; Furman E. G. Edwin Gugovich; et al. (2000, 2000)
Title screen